Safety and tolerability of LBR-101, a humanized monoclonal antibody that blocks the binding of CGRP to its receptor: Results of the Phase 1 program. (June 2014) - Bigal, Marcelo E; Escandon, Rafael; Bronson, Michele; Walter, Sarah; Sudworth, Maria; Huggins, John P; Garzone, Pamela
Background: LBR-101 is a fully humanized monoclonal antibody that binds to calcitonin gene-related peptide. Objective: The objective of this article is to characterize the safety and tolerability of LBR-101 when administered intravenously to healthy volunteers, by presenting the pooled results of the Phase 1 program. Methods: LBR-101 was administered to 94 subjects, while 45 received placebo. Doses ranged from 0.2 mg to 2000 mg given once (Day 1), as a single IV infusion, or up to 300 mg given twice (Day 1 and Day 14). Results: Subjects receiving placebo reported an average of 1.3 treatment-emerging adverse events vs 1.4 per subject among those receiving any dose of LBR-101, and 1.6 in those receiving 1000 mg or higher. Treatment-related adverse events occurred in 21.2% of subjects receiving LBR-101, compared to 17.7% in those receiving placebo. LBR-101 was not associated with any clinically relevant patterns of change in vital signs, ECG parameters, or laboratory findings. The only serious adverse event consisted of "thoracic aortic aneurysm" in a participant later found to have an unreported history of Ehlers-Danlos syndrome. Conclusion: Single IV doses of LBR-101 ranging from 0.2 mg up to 2000 mg and multiple IV doses up to 300 mg were well tolerated. Overt safety concerns have not emerged. A maximally tolerated dose has not been identified.